2001
DOI: 10.1046/j.1365-2982.2001.00286.x
|View full text |Cite
|
Sign up to set email alerts
|

Relaxation of canine gallbladder to nerve stimulation involves adrenergic and non‐adrenergic non‐cholinergic mechanisms

Abstract: Electrical field stimulation (EFS) of dog gallbladder strips induced a frequency-dependent contractile response followed by an off-relaxation that was turned into a pure inhibitory response after atropine pretreatment. Guanethidine reduced the atropine-induced relaxing responses, so an adrenergic mechanism can partially account for the nerve-mediated gallbladder relaxation. However, guanethidine pretreatment also revealed a nonadrenergic noncholinergic (NANC) relaxation induced by EFS, which was frequency inde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 31 publications
1
10
0
Order By: Relevance
“…In the present study, we demonstrated the presence of NOS within neurones of the ganglionated subepithelial plexus which projected to the nonganglionated subepithelial plexus of the gall bladder. This defines for the first time, the source of the NO‐containing nerves of the nonganglionated subepithelial plexus, shown in previous studies, in several species 5,7–9 . This neuroanatomical data suggests a physiological role for NO in modulating gall bladder epithelial function, as has been defined within the gastrointestinal tract 45 .…”
Section: Nitric Oxide and Vasoactive Intestinal Polypeptide In The Resupporting
confidence: 78%
See 1 more Smart Citation
“…In the present study, we demonstrated the presence of NOS within neurones of the ganglionated subepithelial plexus which projected to the nonganglionated subepithelial plexus of the gall bladder. This defines for the first time, the source of the NO‐containing nerves of the nonganglionated subepithelial plexus, shown in previous studies, in several species 5,7–9 . This neuroanatomical data suggests a physiological role for NO in modulating gall bladder epithelial function, as has been defined within the gastrointestinal tract 45 .…”
Section: Nitric Oxide and Vasoactive Intestinal Polypeptide In The Resupporting
confidence: 78%
“…The neurochemical content, including nitric oxide synthase (NOS) and vasoactive intestinal polypeptide (VIP) have been described in gall bladder neurones in several species. 3,[5][6][7][8][9] These intrinsic neurones of the gall bladder regulate its functions, 7,9,10 and we recently demonstrated that gall bladder motility is regulated by neurones of the muscular and serosal plexuses. 3 Notably, the origin of the nerve fibres within the nonganglionated subepithelial plexus, which are probably regulators of gall bladder epithelial function, require characterization.…”
Section: Introductionmentioning
confidence: 99%
“…NANC neurotransmission in the guinea pig gallbladder was described by Mourelle et al [6]. NO is the main NANC neurotransmitter involved in this system [17,18]. EF evokes a gallbladder smooth muscle response by the release of different inhibitory and excitatory neurotransmitters.…”
Section: Discussionmentioning
confidence: 97%
“…Nonadrenergic noncholinergic neurotransmission in guinea pig gallbladder was described more than a decade ago (Mourelle et al, 1993), and NO is the main nonadrenergic noncholinergic neurotransmitter involved (McKirdy et al, 1994b;Alcón et al, 2001). Inflammation evokes a functional impairment in gallbladder nitrergic innervation as demonstrated by the lack of effects of L-NAME in cholecystitic strips compared with control tissue.…”
Section: Discussionmentioning
confidence: 99%